Sensitivity and Specificity of Myocardial Performance Indexing Assessing Acute Right Ventricular Infarction - Karim, Md Rezaul; Rahman, Md Afzalur; Mondol, Rais Uddin; Chowdhury, Tariq Ahmed; Ghose, Rajesh Kumar (TAJ: Journal of Teachers Association, 2022)
The goal of this study was to determine the sensitivity and specificity of the Myocardial Performance Index (MPI)for the assessment of acute right ventricular Infraction. This was a descriptive type of cross-sectional study. The study was carried out in the Coronary Care Unit, Department of Cardiology, Sir Salimulla Medical College, and Mitford Hospital. After exclusion total of 72 patients were included in this study, of which 24 had acute inferior MI with RV involvement diagnosed by ≥ 1mm ST-segment elevation in V3R-V5R of right-sided ECG (group-I) and 48 had acute inferior MI without RV involvement (group-II). All patients underwent echocardiography within 24 hours of admission. The study revealed that RV MPI was significantly increased (0.57± 0.13) in RVMI patients compared to IMI without RVMI (0.24± 0.12). MPI detected RVMI in 08 patients (0.45± 0.09) who did not have ECG findings of RVMI (Group-II). Repeat MPI estimation after 05 days in 21 RVMI (Group-I) and 08 isolated IMI (Group-II) patients who had RVMPI > 0.30showed dramatic reduction of MPI (0.19± 0.07 and 0.22±0.09), respectively. RV MPI ≥ 0.30 has high sensitivity (100%) and specificity (89%) for the diagnosis of RVMI in the presence of acute IMI. The study recommended that MPI may be a new non-invasive echocardiographic gold standard tool in diagnosing acute RVMI and also assessment of right ventricular function in acute inferior myocardial infarction with high sensitivity and specificity. MPI changes can be serially followed in acute RVMI patients to assess changes in RV function. TAJ 2022; 35: No-1: 17-24